Multicentric identities in a globalizing world - Salvatore, Sergio; Gennaro, Alessandro; Valsiner, Jaan (YIS (Series), 2014)
The volume represents the continuing of a the Yearbook of Idiographic Science project, born in 2009 and developed through an annual series of volumes collecting contributes aimed at developing the integration of idiographic and nomothetic approaches in psychology and more in general social science.This year's YIS project received many positive feedbacks and signals of interest, as well as several submissions, from many parts of the world. This fifth volume directs attention to relevant and actual psycho-social phenomena as the development of identity in terms of self identity, social identity and local.identityThe volume is directed to students, researchers and clinicians, interested in deepenig theoretical and methodological issues and improve clinical practices and research cultures.